BMP2 peptide-modified polycaprolactone-collagen nanosheets for periodontal tissue regeneration - Zhang, Yong; Ren, Junxian; Shen, Zongshan; Yang, Jiayu; Yang, Jichen; Lin, Zhengmei; Shi, Xuetao; Zhao, Chuanjiang; Xia, Juan (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionPeriodontitis leads to the degradation of tooth-supporting tissues, ultimately causing tooth mobility and loss. Guided tissue regeneration (GTR) surgery employs barrier membranes to facilitate tissue regeneration. However, conventional membranes lack bone-inducing properties, thereby limiting their efficacy. Our objective was to develop a bifunctional GTR membrane that combines mechanical stability with bone-inducing capabilities. To achieve this, we engineered BMP2 peptide-modified polycaprolactone-collagen nanosheets (BPCNs) to enhance periodontal regeneration by improving cell adhesion, osteogenesis, and anti-inflammatory activity.MethodsBPCNs with nanoscale thickness were fabricated using the spin-coating technique, incorporating BMP2 peptides, collagen, polycaprolactone (PCL), and polyvinyl alcohol (PVA). Successful conjugation of BMP2 to the BPCNs was verified through UV spectrophotometry and confocal laser scanning microscopy. The biocompatibility and cell adhesion properties of BPCNs were rigorously assessed using CCK-8 assays, microscopic imaging, and quantitative cell counting. In vitro osteogenic efficacy was evaluated by Alizarin Red S (ARS) staining and quantitative reverse transcription polymerase chain reaction (qRT-PCR) to analyze osteogenic marker gene expression. A rat periodontal defect model was established to assess in vivo regenerative performance, with outcomes analyzed through micro-CT, hematoxylin-eosin (H&E) staining, and Masson’s trichrome staining, confirming enhanced tissue regeneration and the absence of systemic toxicity. The mechanistic pathways underlying BPCNs-mediated regeneration were elucidated via RNA sequencing (RNA-seq), revealing the activation of osteogenic signaling cascades and the suppression of proinflammatory pathways.ResultsBPCNs demonstrated excellent biocompatibility, promoted fibroblast and bone marrow stem cell (BMSC) adhesion, and enhanced BMSC osteogenesis. Furthermore, BPCNs significantly promoted periodontal tissue regeneration in a rat model. Mechanistically, RNA-seq analysis revealed that BPCNs upregulated genes involved in tissue regeneration and downregulated proinflammatory pathways.DiscussionThis study introduced a novel osteoinductive nanosheet, termed BPCNs, which provides a groundbreaking material-based approach for the regenerative repair of periodontal tissue defects. These findings position BPCNs as a highly promising candidate for GTR surgery, with significant potential to improve clinical outcomes in periodontal regenerative medicine.